A Probabilistic Method for Forensic Cost Estimating of Infrastructure Projects - Signor, R.; Love, Peter; Olatunji, Oluwole; Marchiori, F.; Gripp, W. (Elsevier, 2016)
To determine the existence of overpricing in infrastructure projects a deterministic approach has been typically used by the Brazilian Federal Police. Yet, Judges have often found it too difficult to determine if overpricing had occurred as contractors have tended to claim their projects were ‘unique’ and therefore subjected to price increases. Consequently, Judges have had to consider the likelihood of an error occurring, which has more often led to application of the in 'dubio pro reo' principle. To address the pervasive issue of overpricing in Brazilian infrastructure projects, a novel and robust probabilistic method that utilizes ‘distribution fitting’ using empirical data to forensically determine its occurrence is presented. Considering the limited research that has examined forensic cost estimating in construction, it is promulgated that the proposed approach can be used to support the legal fraternities worldwide to obtain a criminal conviction for overpricing of public infrastructure projects.